PENERAPAN MEDIA KARTU BERGAMBAR PADA WORDWALL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA DISLEKSIA DI SDN SULUK 01 DOLOPO MADIUN - Julaika, Emilia; Mochamad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether the use of picture card media on wordwall can improve the reading ability of dyslexic students. This type of research is descriptive qualitative research, where the resulting data is poured in a descriptive, where the resulting data is poured in a description that describes the overall results of this study. This research was conducted in one of the elementary schools, namely SDN 01 SULUK in Madiun Regency with the subject of 5 students. The result of the research is that picture card media on wordwall can be used for dyslexic students with reading difficulties.